International economics - Appleyard, Dennis R.; Field, Alfred J. (New York, NY : McGraw-Hill Education, 2017)
Appleyard and Field's International Economics provides a balanced treatment of international economics; international trade theory and policy and international monetary theory and policy. Comprehensive and clear, International Economics helps students move beyond recognition toward an understanding of current and future international events, through real world examples featured throughout the text. New improvements covering the emerging issues in the global economy are designed to help readers both understand and appreciate the growing importance of the global economy in their lives.
Includes bibliographical references (p. 765-783) and index.
Keywords: International economic relations; International trade; International finance